The Development of Teaching Materials of Bhineka Tunggal Ika by Integrating Character Education Using Contextual Learning - Siti Kartiani Purba; Reh Bungana Perangin Angin; Anita Yus (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
This research is grounded from the teaching materials which tend to be teacher-centered. Students only listen to what is said by the teacher. This study aims to: (1) develop Bhineka Tunggal Ika teaching materials by integrating effective character education; (2) apply Bhineka Tunggal Ika teaching materials with the integration of character education to improve student learning outcomes using the contextual learning approach. Subjects in this study are students of Class six at state primary school in Medan. The objects in this study are modules developed by Class 6a and 6b respectively 36 students of state primary school in Medan. Data collection instruments used consisted of test learning outcomes and observation of the teacher's ability to manage learning, student character questionnaires and student response questionnaires. The results show that the effectiveness of the product development tools in the application of the development model of Bhineka Tunggal Ika with the integration of character education using contextual learning. Student learning outcomes after the development of Bhineka Tunggal Ika teaching materials with the integration of character education using contextual learning can be seen from the results of student work in completing the given tests, it can be seen that the classical completeness analysis results have reached 94.44%.